Biochemical evidence for diverse strategies in the inner kinetochore - G. E. Hamilton; T. N. Davis (Open Biology, 2020)
The kinetochore is a complex structure whose function is absolutely essential. Unlike the centromere, the kinetochore at first appeared remarkably well conserved from yeast to humans, especially the microtubule-binding outer kinetochore. However, recent efforts towards biochemical reconstitution of diverse kinetochores challenge the notion of a similarly conserved architecture for the constitutively centromere-associated network of the inner kinetochore. This review briefly summarizes the evidence from comparative genomics for interspecific variability in inner kinetochore composition and focuses on novel biochemical evidence indicating that even homologous inner kinetochore protein complexes are put to different uses in different organisms.